2022
DOI: 10.3389/fendo.2022.815063
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Thyroid Diseases and Alzheimer’s Disease in a National Health Screening Cohort in Korea

Abstract: ObjectivesThyroid dysfunction is linked to an increased risk of cognitive impairment. However, studies on the relationships between thyroid diseases and Alzheimer’s disease (AD) have reported conflicting results. We investigated the associations between several thyroid diseases and AD in a nested case-control study.MethodsA total of 1,977 participants with AD were identified by claims data from 2002-2015 among a random sample of half a million people in the Korean National Health Insurance database. We recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 42 publications
0
8
0
2
Order By: Relevance
“…Association of TSH with dementia [ 51 ], suggests that prolonged exposure to low TSH levels could be detrimental to brain function. Individuals with goiter, hypothyroidism, thyroiditis, or hyperthyroidism faced an increased risk of AD, particularly in younger age groups, females, and those with lower comorbidity scores [ 52 ]. This, in turn, suggests that the level of estrogen is associated with thyroid function which was confirmed by studies, including ours, that showed that thyroid disorders are more prevalent in women than in men [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Association of TSH with dementia [ 51 ], suggests that prolonged exposure to low TSH levels could be detrimental to brain function. Individuals with goiter, hypothyroidism, thyroiditis, or hyperthyroidism faced an increased risk of AD, particularly in younger age groups, females, and those with lower comorbidity scores [ 52 ]. This, in turn, suggests that the level of estrogen is associated with thyroid function which was confirmed by studies, including ours, that showed that thyroid disorders are more prevalent in women than in men [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, two downregulated genes such as TTR and LTF in AD were predicted to be involved in thyroid hormone synthesis, amyloid fiber formation, diseases associated with visual transduction, neutrophil degranulation, and canonical retinoid cycle in rods (Twilight Vision) pathways. The downregulation of these two genes may lead to the cognitive impairment, amyloid-beta accumulation and retinal dysfunction and visual impairments due to the disruption in thyroid hormone signaling [45], [46], [47].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, adults are more likely than children to have emotional problems, which usually show up as depression, paranoia, or excitement. It has been said that there is a strong link between hypothyroidism in adults and Alzheimer's disease (48). As people get older, they are more likely to get hypothyroidism, and their risk of getting Alzheimer's disease also goes up a lot.…”
Section: Potential Mechanism Of Cognitive Impairment In Hypothyroidismmentioning
confidence: 99%